Atypical U-shape micro-stacking faults within body-centered tetragonal Zr2Si nanoparticle in silicon modified Zircaloy-4 alloy. (October 2021) - Han, Fuzhou; Yuan, Fusen; Li, Geping; Zhang, Yingdong; Ali, Muhammad; Guo, Wenbin; Ren, Jie; Liu, Chengze; Gu, Hengfei
Abstract: Stacking faults (SFs), which are directly related to partial or incomplete dislocation, have been frequently observed as typical planar defects in crystals with a relatively low stacking fault energy. Generally, stacking faults are unidirectional or intersecting. By using transmission electron microscopy (TEM), we document, for the first time, the presence of atypical U-shape stacking faults within body-centered tetragonal (BCT) structure Zr2 Si nanoprecipitates (NPs) in an as-cast silicon modified Zircaloy-4 alloy (Zr-1.4Sn-0.19Fe-0.11Cr-0.35Si, wt.%). Atomic scale analyses for the characteristics and mechanism of this type stacking faults have been systematically carried out with high resolution TEM (HRTEM). Results reveal the formation mechanism of such stacking faults can be ascribed to the alternate occurences of two non-coplanar stacking faults on (100) and (010) planes. Further, we constructed structure models of planar faults based on atomic resolution HRTEM analysis, which will provide insights on the formation mechanisms of stacking faults with similar configurations. Graphical abstract: Image, graphical abstract